Student Perceptions of Economic Education Through the Implementation of Merdeka Belajar Kampus Merdeka - Dearlina Sinaga; Nova Yunita Sari Siahaan (STAI Hubbulwathan Duri, 2023)
This study aimed to determine whether Merdeka Belajar Kampus Merdeka (MBKM) activities could achieve program goals, assess the implementation of the MBKM program, and examine how MBKM activities were developed and implemented, which included assisting teachers in teaching, supporting school administration, assisting in technology adaptation, and improving skills of students in reading and counting. This research was conducted using qualitative methods. The procedure used in this research is to identify research data sources, collect and evaluate qualitative data, and draw conclusions and suggestions based on qualitative data analysis. The subjects of this study were 27 graduates of the MBKM Batch 2 Economics Study Program. This research helped assist teaching activities in adopting technology by teachers and school administration as well as improving students' literacy and numeracy skills. The results of this study indicate that the implementation of the learning process for MBKM Batch 2 participants, both offline and through home visits, has been running in accordance with the objectives of implementing the Kampus Mengajar (KM). They also pointed out that the implementation of the MBKM in supporting school administration and teachers has been running according to this objective.